A phase II single-arm study of combination pembrolizumab and olaparib in the treatment of patients with advanced biliary tract cancer - Sadagopan, Narayanan; Wang, Hongkun; Yin, Chao; Weinberg, Benjamin Adam; Noel, Marcus Smith; Mukherji, Reetu; Geng, Xue; Marshall, John Lindsay; He, Aiwu Ruth (NPJ precision oncology, 2025)
Effective second-line treatment for advanced biliary tract cancer (BTC) remains an unmet need. BTC often presents with homologous recombination repair (HRR) pathway deficiencies and IDH1/IDH2 mutations which suggest responsiveness to Poly (ADP-ribose) polymerase inhibitors. Thirteen patients were enrolled in our open-label, single-site phase II study of pembrolizumab and olaparib in the second-line setting and beyond for patients with advanced BTC. The objective response rate was 15.4% and the disease control rate was 53.8%. The median progression-free survival (PFS) was 5.45 months (95% CI 1.25-7.82), and the median overall survival was 7.21 months (95% CI 4.5-13.8). Both patients with IDH1 mutations and 2 of the 4 patients with HRR mutations achieved a PFS of at least 7.5 months. All BTC patients do not appear to benefit from pembrolizumab plus olaparib, but those with HRR deficiencies and/or IDH mutations may benefit although it would now represent a rechallenge with immunotherapy. Trial registration: NCT04306367, date of registration 3/10/2020.